Characteristics of Hollow Viscus Injury following Blunt Abdominal Trauma; a Single Centre Experience from Eastern India - Nawal Jha; Sanjay Yadav; Rajshekhar Sharma; Dipendra Sinha; Sandip Kumar; Marshal Kerketta; Mini Sinha; Abhinav Anand; Anjana Gandhi; Satish Ranjan; Jitin Yadav (Bulletin of Emergency and Trauma, 2014)
Objective: To determine the presentation, anatomical distribution, diagnostic method, management and outcome of hollow viscus injury (HVI) from blunt abdominal trauma.Methods: This was a retrospective cross-sectional study including patients with blunt abdominal trauma leading to HVI admitted at Rajendra Institute of Medical Sciences, Ranchi, over a period of 4.5 years (January 2009 to July 2014). Data were retrieved from patients’medical records. Total 173 patients with HVI due to blunt abdominal trauma, who underwent laparotomy at our institute, were reviewed. Data regarding clinical presentation, anatomical distribution, management and outcome were recorded and analysed.Results: Out of 173 patients 87.1% were men and 12.9% were women. Mean age of patients was 29 ± 14.02 years. The most common site of injury was ileum (46.2%) followed by jejunum (44.5%). There were 5 gastric perforations (2.9%), 2 (1.15%) duodenal, 2 (1.15%) colonic, 2 (1.15%) sigmoidal and 2 (1.15%) rectal injuries. One caecal injury was also recorded. Road traffic accident was the most common mechanism of injury (57.2%) followed by fall from height (36.4%) and assault (6.4%). Free gas under diaphragm on erect abdomen radiography was seen in 85.5% of cases while preoperative CT Abdomen was done in 11.6% of cases. Treatment consisted of simple closure of the perforation (66.5%), resection and anastomosis (11.0%) and stoma (22.5%). Major complication was anastamotic leak which was recorded in 6.4% cases and 15.6% patients developed burst abdomen. Average hospital stay was 13 ± 6 days. Overall mortality rate was 12.7%.  Conclusion: Although early recognition of intestinal injuries from blunt abdominal trauma may be difficult in all cases, it is very important due to its tremendous life threatening potential. Age of the patient, anatomical site and time of presentation are probably main prognostic factors.